2015
DOI: 10.1002/aenm.201501636
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Transition Metal Oxide–Sulfur Interactions for Long Life Lithium Sulfur Batteries: The “Goldilocks” Principle

Abstract: The lithium‐sulfur battery is a compelling energy storage system because its high theoretical energy density exceeds Li‐ion batteries at much lower cost, but applications are thwarted by capacity decay caused by the polysulfide shuttle. Here, proof of concept and the critical metrics of a strategy to entrap polysulfides within the sulfur cathode by their reaction to form a surface‐bound active redox mediator are demonstrated. It is shown through a combination of surface spectroscopy and cyclic voltammetry stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
513
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 688 publications
(528 citation statements)
references
References 50 publications
(100 reference statements)
15
513
0
Order By: Relevance
“…Based on the discoveries in the last 10 years it has been found that cathode architecture is vital and active sulfur must be either pre-confined into a conductive host least permeable to polysulfide dissolution [4][5][6][7] or an strongly polysulfide binding compound should be dispersed into the cathode network, [8][9][10][11][12][13] otherwise both the utilization of sulfur and cycling performance will suffer. Furthermore, the combination of the above two approaches is also reported.…”
Section: -3mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the discoveries in the last 10 years it has been found that cathode architecture is vital and active sulfur must be either pre-confined into a conductive host least permeable to polysulfide dissolution [4][5][6][7] or an strongly polysulfide binding compound should be dispersed into the cathode network, [8][9][10][11][12][13] otherwise both the utilization of sulfur and cycling performance will suffer. Furthermore, the combination of the above two approaches is also reported.…”
Section: -3mentioning
confidence: 99%
“…1,2 However, the tendency for partially reduced sulfur to form soluble polysulfides that lead to fast capacity fade and low coulombic efficiency, the insulating nature of sulfur and Li 2 S, and the considerable volume change ∼80% between these two end products all put inevitable constraints on electrode architecture and cell level designs in attempts to approach or achieve these appealing theoretical values. [1][2][3] Based on the discoveries in the last 10 years it has been found that cathode architecture is vital and active sulfur must be either pre-confined into a conductive host least permeable to polysulfide dissolution [4][5][6][7] or an strongly polysulfide binding compound should be dispersed into the cathode network, [8][9][10][11][12][13] otherwise both the utilization of sulfur and cycling performance will suffer. Furthermore, the combination of the above two approaches is also reported.…”
mentioning
confidence: 99%
“…[12][13][14] However, one disadvantage of using these additives is that most of them do not contribute any capacity in the voltage range (1.6 V-3.0 V) used in the Li-S battery. This leads to a reduction in practical energy density at the cell level.…”
mentioning
confidence: 99%
“…In parallel, a different route has also been frequently taken by researchers to mitigate polysulfide dissolution chemically. A wide variety of compounds have been found or designed to show strong interactions with polysulfide through acid-base or redox processes to temporarily adsorb the polysulfide, [9][10][11][12][13][14] which slows down the outward diffusion of polysulfide from porous cathode and the associated loss of active material, reducing the shuttling effect, and decelerating the capacity fade. This concept still allows the generation of polysulfide intermediates in the porous composite electrode's liquid electrolyte network to partially preserve the liquid redox cell character.…”
mentioning
confidence: 99%
“…First of all, the metal compounds should have strong interactions with polysulphides. According to the relative research by Nazar, 162 the metal oxides with a moderate voltage (versus Li/Li 1 ), which form surfacebound thiosulfate via redox, are the most suitable for chemically binding polysulphides. TiO 2 , and MnO 2 both display these characteristics.…”
Section: Summary and Perspectivementioning
confidence: 99%